Xiao-Shen-Formula, a Traditional Chinese Medicine, Improves Glomerular Hyper-Filtration in Diabetic Nephropathy via Inhibiting Arginase Activation and Heparanase Expression - An, Xiaofei; Zhang, Maoxiang; Zhou, Sisi; Lu, Tian; Chen, Yongjun; Yao, Lin (Frontiers in Physiology, 2018)
Hyperglycemia induces glomerular hyper-filtration, which contributes to the development of diabetic nephropathy (DN), a condition that remains a challenge for treatment. The present study investigated the effect of Xiao-Shen-Formula (XSF) used for treatment of renal injury in type 1 DN mice model induced by streptozotocin (STZ) and its underlying mechanism in cultured human glomerular endothelial cell (hGECs). Studies were performed using control group, diabetic DN, DN treated with XSF groups (1g/kg/d, LXSF or 3g/kg/d, HXSF) for 6 weeks and hGECs were post-treated with mice serum containing HXSF (MS-HXSF) and arginase inhibitor (ABH, 100 M) in high glucose medium. HXSF treatment restored STZ-induced renal hyper-filtration, glomerulosclerosis, renal microvascular remodeling and the increased levels of systemic reactive oxidative species and inflammatory cytokines, companied by preventing the decreased expression of glomerular heparin sulfate and the increased levels of cortical heparanase and argianse2 protein and arginase activity. In hGECs study, MS-HXSF ameliorated the enhancement in arginase activity, the protein/mRNA expression of heparanase, mRNA levels of vascular cell adhesion molecule-1, intercellular adhesion molecule-1, monocyte chemoattractant protein-1 and permeability of hGECs monolayers as well as the depression of nitric oxide production. Besides all these protective effect, XSF blunted the mRNA expression of TNF-α in vivo and vitro studies as well, which is not changed by the post-treatment of ABH or HXSF plus ABH. This study demonstrated that the protective effect of XSF might be related with vascular prevention, anti-inflammation and anti-oxidation through intervening multi-targets including glomerular endothelial arginase-heparanase signaling pathway in DN model.